Studying the Generational Relations Challenges from the Viewpoint of Female Students 20 to 26 Years of a Public University - Sedigheh Abbasi; khadijeh safiri; amirmasoud amirmazaheri (توسعه اجتماعی, 2019)
The present paper is the result of a qualitative research using grounded theory method in order "to examine the challenges of generational relations from the viewpoint of female students of a government university and their strategy of exposure to this phenomenon." Using a theoretical sampling, 15 female students aged 20 to 26 years old at Alzahra University were selected using snowball method. Theoretical saturation was achieved after 5 deep interviews with students-each interview was about 45 to 60 minutes-. The conceptual literature of the research is theories: “Agborn, Toffler, Raizman, Giddens, McLuhan, and Dick Hebdige”. The central issue is the "idealist look, independence and individual decision making," according to which young girls are different in their knowledge, attitudes, attitudes and behavior with their parents. Young girls look at things with an idealistic look and choose to vote; while their parents have been defending everything with a conservative attitude. In other words, in the middle class society, changes have taken place in terms of social processes, and in the micro level, with changes in the personality traits of young girls, there is a cultural and personality change and we face a distinct generation.